The Impact of Social Media on the Mental State of Polish Students at the University of Warsaw - Opolska-Bielańska, Agata (Roczniki Nauk Społecznych, 2025)
In the era of growing popularity of social media, it is important to understand their impact on the mental state of their users. Social media have become a key communication tool of the 21st century and an integral part of interpersonal relationships. They are used to share information, distribute content, promote social initiatives. However, the rapid influx of digital content exceeds the cognitive capabilities of the users, which leads to anxiety, stress and problems with mental state. The article analyzes the impact of social media on the mental state of their users, based on a literature review and a CAWI survey conducted among 190 respondents aged 18–40. The participants of the study were students of the University of Warsaw, who were invited to participate in the study and informed about the topic and purpose of the study. The results indicate a lack of conscious control over the time spent on social media and a variety of emotions depending on the content consumed, with a predominance of positive emotions. At the same time, constant exposure to social media leads to cognitive fatigue and a general deterioration in well-being, with a dominant preference for personal social interactions.